OPTIMAL RESOLUTION FOR AUTOMATIC QUANTIFICATION OF BLOOD VESSELS ON DIGITIZED IMAGES OF THE WHOLE CANCER SECTION - Françoise, Ronan; Michels, Jean-Jacques; Plancoulaine, Benoît; Herlin, Paulette (Image Analysis and Stereology, 2011)
Discrepancies concerning the prognostic significance of cancer vascularization can be partly explained by biases due to quantification protocols. We recently recommended a swift, inexpensive and automatic analysis of 2,700 dpi slide scanner images of the whole immunostained sections. Another team, proposed, quite at the same time, to work at 4,000 dpi. The aim of the present paper is to check if information contained in images scanned at 2,700 and 4,000 dpi are relevant and equivalent, when compared to the low magnification of the microscope, in order to propose the best compromise between precision and time expense. To evaluate precisely the amount of information gained or lost according to the resolution used, we compared the number and size of blood vessel profiles, manually detected, on twenty one Hodgkin lymphoma acquired with a scanner (2,700 and 4,000 dpi) and with a microscope (16,000 dpi). Results obtained at 4,000 dpi were equivalent to the estimation performed at microscopical level either by a biologist or a pathologist, while tiny vessels were lost at 2,700 dpi. Scanning whole histological sections at 4,000 dpi provides a relevant method for evaluating tumour vascularization, which can be easily automated and standardized.